If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 24 = 0 Reorder the terms: 24 + 3n = 0 Solving 24 + 3n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 3n = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 3n = 0 + -24 3n = 0 + -24 Combine like terms: 0 + -24 = -24 3n = -24 Divide each side by '3'. n = -8 Simplifying n = -8
| x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 | | 10(1-p)=10(p+9) | | 12u+17y=891 | | 36b-9=18b+3 | | 27-2x=x | | 5+2r=26 | | (3x+2y)2= | | 13xsquared+26x+14=0 | | -12+10x=9x+13 | | -22(x+1)=-11(x+2) | | 9-2g=-5 | | 36b-1=18b+3 | | 2.5x+3.5=-3.5 | | 4t^2-17t=15 | | -12(x-2)=4(x+6) | | 3x-(2x+7)=4x+2 | | 4x-2-4=9+x | | 2(m-3)+5=11 | | 2f+4f-9=27 | | -18n+8=-17n-2 | | 200-4p=-10+8p | | 1+12x-2x=-9 | | 4(x+1)+3=-6x-1 | | -81-4x=-11x+101 | | 23.67(8.25-x)=15.4(4.45+x) | | -5(2b+2)=30-2b |